Adopting blockchain technology by Finnish energy companies for managing suppliers' relationships : Drivers, barriers and potential performance outcomes - Toivomäki, Eetu (My University, 2026)
The global energy sector is undergoing a structural transformation characterized by decentralization, digitalization, and the expansion of renewable energy systems. This transformation has increased the complexity of upstream supplier-buyer relationships, creating a need for governance mechanisms that can ensure transparency, traceability, and trust across multi-tier supply networks. Blockchain technology has been identified as a potential solution to these governance challenges, yet scholarly understanding of its adoption within the energy sector remains fragmented. Existing studies have examined drivers, barriers, or performance outcomes in isolation, whereas no integrated study has examined all three dimensions in the context of energy companies managing their supplier relationships. This thesis addresses that gap by investigating the drivers, barriers, and performance outcomes of Finnish energy companies' adoption of blockchain technology to manage supplier relationships. A conceptual model comprising 24 propositions was developed from the literature, drawing on transaction cost economics, social exchange theory, resource dependence theory, and the technology-organization-environment framework, and empirically examined through a qualitative multiple-case study of four Finnish energy-sector organizations using semi-structured interviews analyzed with thematic analysis guided by abductive reasoning. The findings confirm that supply chain traceability and sustainability compliance are the most compelling value propositions of blockchain for energy-sector supplier management, while the absence of internal blockchain expertise and the difficulty of demonstrating return on investment emerged as the most significant barriers. Scalability limitations and regulatory concerns received less support than the literature anticipates. On performance outcomes, sustainability compliance capacity was the dominant anticipated benefit for firms facing direct reporting obligations, cost-reduction potential was acknowledged but tempered by uncertainty about net returns, and relationship improvement was endorsed most strongly for complex multi-tier partnerships. Learning, decision-making, and communication outcomes were supported but conditional on the firm's level of digital maturity. Four emergent factors were identified beyond the original framework: the crowding-out effect of AI on blockchain's innovation agenda, the necessity of industry consortium coordination, the moderating role of firm size and digital maturity, and the need for a prior relational mindset shift among supply chain partners. For practitioners, the study recommends anchoring blockchain initiatives around sustainability traceability use cases, building internal competence before committing to platforms, and pursuing collaborative industry approaches rather than individual company efforts.

Globaali energia-ala on käymässä läpi rakenteellista muutosta, jolle ovat ominaisia hajauttaminen, digitalisaatio ja uusiutuvien energialähteiden laajentuminen. Tämä muutos on lisännyt toimittajien ja ostajien välisten suhteiden monimutkaisuutta, mikä on luonut tarpeen hallintomekanismeille, joilla voidaan varmistaa läpinäkyvyys, jäljitettävyys ja luottamus monitasoisissa toimitusketjuissa. Lohkoketjuteknologia on tunnistettu potentiaaliseksi ratkaisuksi näihin hallintahaasteisiin, mutta sen käyttöönotosta energia-alalla on edelleen hajanaista tieteellistä tietoa. Olemassa olevat tutkimukset ovat tarkastelleet ajureita, esteitä tai suorituskykyvaikutuksia erillään toisistaan, eikä yksikään integroitu tutkimus ole tarkastellut kaikkia kolmea ulottuvuutta energiayhtiöiden toimittajasuhteiden hallinnan kontekstissa. Tämä opinnäytetyö täyttää tämän aukon tutkimalla suomalaisyritysten lohkoketjuteknologian käyttöönoton ajureita, esteitä ja suorituskykyä toimittajasuhteiden hallinnassa. Kirjallisuuden pohjalta kehitettiin 24 väitettä kattava käsitteellinen malli, joka perustuu transaktiokustannustalouteen, sosiiaalisen vaihdon teoriaan, resurssiriippuvuusteoriaan sekä teknologia-organisaatio-ympäristö-viitekehykseen. Väitteitä tutkittiin empiirisesti neljän suomalaisen energia-alan organisaation kvalitatiivisessa monitapaustutkimuksessa puolistrukturoitujen haastattelujen avulla ja aineisto analysoitiin abduktiiviseen päättelyyn perustuvalla temaattisella analyysillä. Tutkimustulokset osoittavat, että toimitusketjun jäljitettävyys ja vastuullisuusraportoinnin tukeminen ovat lohkoketjuteknologian vahvimmat käyttötapaukset energia-alan toimittajasuhteiden hallinnassa, kun taas sisäisen lohkoketjuosaamisen puute ja investoinnin kannattavuuden osoittamisen vaikeus nousivat merkittävimmiksi esteiksi. Skaalautuvuusrajoitteet ja sääntelyyn liittyvät huolet saivat kirjallisuudessa vähemmän tukea. Suorituskykyvaikutuksista vastuullisuusraportoinnin tukeminen nousi hallitsevaksi odotetuksi hyödyksi erityisesti yrityksille, joille suorat raportointivelvoitteet ovat voimassa. Kustannussäästöpotentiaali tunnistettiin, mutta sitä varjosti epävarmuus nettohyötyjen toteutumisesta ja toimittajasuhteiden parantumista kannatettiin vahvimmin monitasoisissa ja monimutkaisissa kumppanuuksissa. Oppimiseen, päätöksentekoon ja viestintään liittyvät vaikutukset saivat tukea, mutta ne olivat ehdollisia yrityksen digitaalisen kypsyyden tasolle. Alkuperäisen viitekehyksen ulkopuolelta tunnistettiin neljä uutta tekijää: tekoälyn syrjäyttävä vaikutus lohkoketjun asemaan innovaatioagendalla, toimi-alakonsortion välttämättömyys käyttöönoton onnistumiselle, yrityksen koon ja digitaalisen kypsyyden moderoiva rooli sekä tarve toimitusketjukumppaneiden väliseen asennemuutokseen kohti yhteistyöhakuisempaa suhdetta. Käytännön suosituksina tutkielma ehdottaa lohko-ketjuhankkeiden ankkuroimista vastuullisuuden jäljitettävyyteen liittyviin käyttötapauksiin, sisäisen osaamisen rakentamista ennen alustavalintoja sekä yhteistyöhön perustuvien toimi-alamallien suosimista yksittäisten yritysten erillishankkeiden sijaan.
Keywords: blockchains; supply chains; enterprises; barriers; technology; trust; leadership (activity); technology companies; energy management; digitalisation; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business